Uncertainty Volatility, Investment, And Cash Holding In ASEAN Countries - Marcella Roring; Rita Juliana (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
This study aims to show the effect of uncertainty on firms’ corporate investment and cash holding in five ASEAN countries, namely Malaysia, Indonesia, Singapore, Thailand, and Vietnam. The study was conducted using data from non-financial public listed firms in these five ASEAN countries during the 2006 to 2020 period. The uncertainty volatility is measured using the standard deviation of the economic policy uncertainty index. The results of this study find that uncertainty volatility increases corporate investment and decreases corporate cash holding. This result indicates that high uncertainty economic condition cause firms to invest to reduce information asymmetry by giving signals to external investors through investment, and as result, it reduces the corporate cash holdings. Moreover, we also find that uncertainty volatility is more economically significant than Economic Policy Uncertainty it self. It is possible that uncertainty volatility can better capture the real uncertain condition in the economy.